Solomon Islands : Third Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Staff Report; Press Release; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Solomon Islands' Third Review Under the Extended Credit Facility (ECF) Arrangement and Request for Modification of Performance Criteria (PC). Program performance under the ECF arrangement has been broadly satisfactory. Reserve buffers have been rebuilt and are at a comfortable level, well above the average of other small states. All PCs for end-December, the indicative targets (ITs) for March, and the continuous PCs were met with considerable margins, except for the IT on government-funded recurrent spending on health and education, which was narrowly missed. Based on Solomon Islands' program performance, the IMF staff recommends completion of the third review under the ECF-supported program.